2012
DOI: 10.1002/pro.2141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on formation of perfect tau fragment fibrils using PRIME20/DMD simulations

Abstract: We investigate the fibrillization process for amyloid tau fragment peptides (VQIVYK) by applying the discontinuous molecular dynamics method to a system of 48 VQIVYK peptides modeled using a new protein model/force field, PRIME20. The aim of the article is to ascertain which factors are most important in determining whether or not a peptide system forms perfect coherent fibrillar structures. Two different directional criteria are used to determine when a hydrogen bond occurs: the original H-bond constraints an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…In PRIME20, the known backbone -angles, C␣-C␣ distances and L-isomerization constraints on each amino acid are modeled by imposing pseudo-bonds between the relevant beads. A non-biased distancebased criterion is used to judge when directional hydrogen bonds are formed and broken (50). Glycine does not have a side chain bead, and proline cannot form backbone hydrogen bonds with other residues.…”
Section: Dmd-mentioning
confidence: 99%
“…In PRIME20, the known backbone -angles, C␣-C␣ distances and L-isomerization constraints on each amino acid are modeled by imposing pseudo-bonds between the relevant beads. A non-biased distancebased criterion is used to judge when directional hydrogen bonds are formed and broken (50). Glycine does not have a side chain bead, and proline cannot form backbone hydrogen bonds with other residues.…”
Section: Dmd-mentioning
confidence: 99%
“…Also, Lew and coworker found that the VQIVYK and VQIINK segments mediate the possible generation of oligomeric structures [12]. Similar computational results were found by Cheon et al They revealed potential oligomeric formations of tau proteins through the replica exchange molecular dynamics (REMD) method [14]. Also, Shea group reported the formation of tau proteins with b-sheet characteristic after deleting of the 287 th lysine residue with additional residues [15].…”
Section: Introductionsupporting
confidence: 54%
“…Similarly, Shea group investigated the stability of polymorphic Ab 9-40 fibrils according to the stacking and facing directions of subunit fibrils structures based on subunit fibrils [22]. For tau proteins, Cheon et al, investigated the diverse kinds of generated tau protein and their thermodynamic stabilities through the REMD methods [14].…”
Section: Introductionmentioning
confidence: 99%
“…A similar resolution model, PRIME (and the more recent PRIME20), has been employed extensively by Hall and colleagues (17,(91)(92)(93)(94)(95)(96) to study the kinetics of fibril formation (Figure 5d ). They used discontinuous molecular dynamics (DMD), which allows for discontinuous breaks in the energy functional by computing the reflection/transmission of particles across the discontinuity.…”
Section: The Prime Model and Discontinuous Molecular Dynamicsmentioning
confidence: 99%
“…Fibrils for this system formed by the intermediate of amorphous aggregates that, given sufficient size, spontaneously ordered into β sheets (i.e., the nucleation growth mechanism), which subsequently extended by the addition of monomers to the ends, one at a time (templated assembly). They also simulated the fibrillization of 48 tau fragment peptides (sequence VQIVYK) at varying temperatures (92). They contrasted two hydrogen bond constraints: one favoring parallel β sheets and one with no bias to parallel versus antiparallel.…”
Section: The Prime Model and Discontinuous Molecular Dynamicsmentioning
confidence: 99%